2015
DOI: 10.1084/jem.20151468
|View full text |Cite
|
Sign up to set email alerts
|

Transformative tools for tackling tuberculosis

Abstract: Better tools are needed for detecting Mycobacterium tuberculosis and defining the dynamic interactions of M. tuberculosis with its human host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…To develop such predictive tests, we need transformative research that will enable us to identify biomarkers or biosignatures that can resolve the LTBI spectrum (8) and help target those at highest risk of progressing to active disease (51). Some promising biomarkers have been identified, especially gene expression signatures (52), but much more validation work is required.…”
Section: Discussionmentioning
confidence: 99%
“…To develop such predictive tests, we need transformative research that will enable us to identify biomarkers or biosignatures that can resolve the LTBI spectrum (8) and help target those at highest risk of progressing to active disease (51). Some promising biomarkers have been identified, especially gene expression signatures (52), but much more validation work is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, translation from biomarker discovery to clinical tools has been poor. In this regard, improved detection of the lipoglycan biomarker LAM could lead to a breakthrough in urine‐based antigen detection . Another approach to TB biomarkers is the analysis of mycobacteria‐specific lipid profiles.…”
Section: Challenges and Future Directions For Improving The Diagnosismentioning
confidence: 99%
“…As previously shown (5), in HIV-uninfected persons, HLA-DR, Ki67, and CD38 expression on IFN-g 1 Mtb-specific CD4 1 T cells was significantly higher in aTB participants than in those with LTBI ( Figure 1B). Interestingly, although HLA-DR expression on Mtb-specific CD4 1 T cells in the LTBI/HIV 1 group (median, 41.7%; IQR, 25.7-54.6%) was significantly higher than in the LTBI/HIV 2 group (median, 13.7%; IQR, 8.9-27.5%), HLA-DR expression on these cells was significantly further increased in HIV-infected individuals with aTB (median, 84%; IQR, 73.7-87.9%) ( Figure 1B). Additional analyses showed that in LTBI/HIV 1 individuals, HLA-DR expression on Mtb-specific CD4 1 T cells mirrors HLA-DR expression in the whole CD4 compartment (P = 0.02; r = 0.56), but this association was not apparent in aTB/HIV 1 individuals (data not shown).…”
mentioning
confidence: 99%